The Cambridge history of African American literature - Graham, Maryemma; Ward, Jerry Washington (Cambridge University Press, 2011)
"The first major twenty-first century history of four hundred years of black writing, The Cambridge History of African American Literature presents a comprehensive overview of the literary traditions, oral and print, of African-descended peoples in the United States. Expert contributors, drawn from the United States and beyond, emphasise the dual nature of each text discussed as a work of art created by an individual and as a response to unfolding events in American cultural, political, and social history"--Provided by publisher.